1978
DOI: 10.1093/nar/5.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of chromatin by differential solubility in dilute salt

Abstract: Chromatin prepared from the livers of rats was fractionated on the basis of solubility in dilute NaCl. Neither of the fractions obtained was enriched in newly synthesized DNA. The salt-soluble fraction had a higher protein content (usually up to 50%) relative to the DNA, and contained 72% or more of the rapidly synthesized RNA. This RNA was found to be complexed with the salt-soluble deoxyribonucleoprotein, not merely co-solubilized with it. Also, polylysine-binding studies showed that about 70% or more of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1980
1980

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It may be excluded, however, that this fraction would be the actively transcribed portion of chromatin. Hybridization studies with cDNA transcribed frorti liver polysomal mRNA have shown that the fraction of chromatin most readily digestible with micrococcal nuclease is not enriched in active chromatin (Itzhaki et al, 1978). Secondly, the isolated oligonucleosomes were not remarkable with respect to protein composition (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be excluded, however, that this fraction would be the actively transcribed portion of chromatin. Hybridization studies with cDNA transcribed frorti liver polysomal mRNA have shown that the fraction of chromatin most readily digestible with micrococcal nuclease is not enriched in active chromatin (Itzhaki et al, 1978). Secondly, the isolated oligonucleosomes were not remarkable with respect to protein composition (cf.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that one deals with a special portion of chromatin. On the other hand, there are reports on salt-soluble oligonucleosomes(Itzhaki et al, 1978;Campbell & Cotter, 1977;Wittig & Wittig, 1977;Whitlock & Simpson, 1976;Renz et al, 1977;Lewis et al, 1976; Stratling et al, 1978a,b). Also, the "solubility" of oligonucleosomes depends on the chromatin concentration and the chain length(Campbell & Cotter, 1977; Wittig& Wittig, 1977).…”
mentioning
confidence: 99%